(untitled) (Bangladesh Journal of Agricultural Research, 2011)
Twenty eight rice genotypes were evaluated for their stability in respect of grain yield and growth duration during boro season of 2007-08 over five locations viz. Gazipur, Jamalpur, Comilla, Jinaidhah, and Rajshahi. Variances for genotypes, locations, and G × E interactions were significant for both the traits. Linear components of G × E interactions were insignificant but non- linear components (pooled deviation) were significant. Considering stability parameters (bi and S2 di) for days to maturity, genotypes Raja, Ropa-1, and Sera were least responsive to environment (bi =1) and minimum deviation from regression (S2 di = 0) were stable over the locations. The estimates of stability parameters for grain yield revealed that the genotypes Ropa-1, SL-8, Lily and Sera were higher grain yielder, b value were close to the unity and S2di value were near to the zero. So, these four genotypes could be considered as the most stable over the environments. Considering both growth duration and grain yield based on stability parameters, the genotypes Ropa and Sera were identified as most stable and could be recommended for release as varieties. Key words: Hybrid rice; stability; exotic. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9233 BJAR 2011; 36(1): 97-102